Evidence and implications of non-tradability of food staples in Tanzania 1983-1998 - Delgado, Christopher L.; Minot, Nicholas; Tiongco, Marites M. (International Food Policy Research Institute, 2004)
Economic reform programs assume that major goods are tradable, such that depreciation of the real exchange rate raises the value of output compared to factor costs in domestic currency. In Tanzania, major food staples that account for most real income are non-tradables in at least one-quarter of the country. This is demonstrated and implications assessed for the constraints imposed on macroeconomic-led adjustment strategies.